2010
DOI: 10.1111/j.1747-0765.2010.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil iron fractionation and availability at selected landscape positions in a loessial gully region of northwestern China

Abstract: Soil Fe fractions and availability vary with landscape positions, because landscape position affects soil chemical properties and water conditions. In the present study, we investigated Fe fractions and availability at selected landscape positions in the loessial gully region of northwestern China. Four landscape positions, plateau, slope, terrace, and gully bottom were investigated. For each landscape position, soil samples were collected at 20-cm increments to a depth of 80 cm. Iron in the soil samples was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…, should really be narrower. Dry matter production and leaf concentration and content of Fe correlated positively with Fe p content (Equations 54, 55, and 56), indicating that the Fe fraction bound to the organic components of the soil was what most contributed to availability of the element to the plant, as found by Wei et al (2010).…”
Section: Resultsmentioning
confidence: 78%
“…, should really be narrower. Dry matter production and leaf concentration and content of Fe correlated positively with Fe p content (Equations 54, 55, and 56), indicating that the Fe fraction bound to the organic components of the soil was what most contributed to availability of the element to the plant, as found by Wei et al (2010).…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, Guo et al (2006) found that most Fe in surficial sediments was in the residual fraction. Wei et al (2010) observed that in most soil of the loessial gully region of northwestern China, Fe was in association with the mineral bound fraction (73-96%). Some chemical forms of metals such as SolEx-Fe, Car-Fe, and Om-Fe can be considered as reactive forms since these are readily available or potentially available forms (Ma & Uren 1998;Pietrzak & McPhail 2004).…”
Section: Chemical Forms Of Fementioning
confidence: 96%
“…However, CFeox-Fe was higher in the soils beneath canopy of all plants as compared to their interspace soils (Figure 2). Oxides forms of Fe may consider as indirect source of available Fe (Wei et al 2010) or as poorly available Fe (Walna et al 2010).…”
Section: Chemical Forms Of Fementioning
confidence: 99%
“…Fe is one of the major constituents of the lithosphere and pedosphere. The content of Fe in natural soils ranges between 7 and 42 mg/g (Wei et al, 2010). However, plant available Fe is low in most soils because the low solubility product of iron minerals makes the inorganic form of iron unavailable to plants and forms the most common widespread nutritional disorder world over (Chatterjee et al, 2006).…”
Section: Variations In Basic Soil Chemical Characteristicsmentioning
confidence: 99%